Development of organosilane-containing bioorganometallic compounds evaluated as antiparasitic agents against Plasmodium falciparum and Trichomonas vaginalis - Adams, Muneebah (Department of Chemistry, 2016)
Many successful initiatives have been employed to stem the spread of the diseases such as malaria and trichomonas's. However, in cases where infection has occurred, pharmaceutical treatments are required. A problem seen across the board is the development of resistance to known treatments. An even bigger problem has been the development of resistance to promising compounds during the clinical trial phase. This has led to the need for effective treatments which are able to overcome the resistance problem. This study investigated the synthesis, characterisation and pharmacological evaluation of new bioorganometallic organosilane-containing compounds based on thiosemicarbazone (TSC),quinoline and benzothiazole scaffolds. Selected thiosemicarbazone-containing ruthenium(II), rhodium(III) and palladium(II) metal complexes were also studied. The compounds were screened for antiplasmodial and antitrichomonal activity, along with their activity against A2780 human ovarian carcinoma and WHCO1 oesophageal cancer cell-lines.